2015
DOI: 10.14712/23362936.2015.53
|View full text |Cite
|
Sign up to set email alerts
|

Envenoming by Crotalid Snake Chinese Moccasin Agkistrodon Acutus Bite – A Case Report

Abstract: Although the bites caused by snakes from former Agkistrodon family in the areas of occurrence are not rare and even have certain epidemiologic importance, in case of envenoming by Deinagkistrodon acutus the clinical studies and case reports are very sporadic. This case report describes the envenoming of a private snake breeder bitten by young Chinese moccasin Deinagkistrodon acutus to the thumb of his left hand. He sought for a medical help immediately after snakebite. Patient presented with a local oedema on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…We reviewed the reported case of D . acutus envenomation in Table 1 [4,12‐24]. 82.29% (302/367) of these cases showed abnormalities in platelet counts.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We reviewed the reported case of D . acutus envenomation in Table 1 [4,12‐24]. 82.29% (302/367) of these cases showed abnormalities in platelet counts.…”
Section: Discussionmentioning
confidence: 99%
“…Deinagkistrodon acutus ( D. acutus ) belongs to the Viperidae family, Crotalinae subfamily and Deinagkistrodon genus (containing only D. acutus ), with widespread distribution throughout the south‐eastern parts of China, northern Vietnam, and Laos [4]. The mortality rate of D. acutus envenomation remains high in China, at approximately 24% [5].…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, severe coagulopathy and thrombocytopenia are the main laboratory findings of D. acutus envenomation in addition to serious wound complications and systemic bleeding [11–13]. Valenta et al [15] reported a victim of D. acutus bite who developed incoagulable blood between 1.5 and 7 h post-bite. Hung et al [13] reported the case of a man with persistent thrombocytopenia 44 h after envenomation; his platelet level was normal 30 min post-bite.…”
Section: Discussionmentioning
confidence: 99%
“…In case 1, thrombocytopenia did not show improvement after antivenom therapy, which was probably attributable to uncontrolled infection. Nevertheless, Valenta et al [15] reported a single case of D. acutus envenomation who manifested severe coagulopathy in the absence of thrombocytopenia. Therefore, the exact mechanism of thrombocytopenia in D. acutus snakebite remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Animal venoms are considered as one of the most important sources for drug development [ 7 ]. D. acutus (Chinese moccasin or five-pace snake) is considered as the monovalent genus Deiagkistrodon previously classified into one genus Agkistrodon , which lives mainly in southeast China, North Vietnam, Laos, and Taiwan [ 8 ]. D. acutus envenomation causes hemocoagulation disorder, which causes the symptoms of hemorrhage and microthrombi formation.…”
Section: Introductionmentioning
confidence: 99%